What’s the “Use” of Student Ratings of Instruction for Administrators? One University’s Experience - Beran, Tanya; Violato, Claudio; Kline, Don (Canadian Journal of Higher Education, 2007)
At most Canadian and American community colleges and universities, student ratings have been implemented as a means of evaluating course instruction. Although concerns regarding the validity of student ratings from instructors’ perspectives have been studied quite extensively, issues associated with the use of student ratings information by administrators have been largely ignored. In this study, we surveyed 52 administrators at a major Canadian university about the types of ratings they use, how useful they are, and their purpose. Our findings indicate that administrators are interested in knowing about instructor characteristics and teaching procedures. In addition, ratings are being used for instructor and department evaluation as well as scheduling courses. In general, administrators regard student ratings positively and think that they are useful. However, they have some reservations. Dans la majorité des collèges et des universités, les étudiants évaluent leurs professeurs. Les inquiétudes de la validité de ces évaluations selon les professeurs, ont été bien etudiées, mais l’utilization et les perspectives des administrateurs n’ont pas été etudiées. Dans cet étude 52 adminstrateurs dans une grande université Canadienne ont répondu aux questions selon les evaluations. Les résultats indiquent que les administrateurs s'intéressent aux caractéristiques des professeurs et de leurs apprentissages. De plus, les administrateurs utilisent les évaluations pour organiser les cours. En general, les administrateurs ont donné des réponses très positives avec peu de réservations.